2020
DOI: 10.1016/j.mayocpiqo.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biopsy Technique on Clinically Important Outcomes for Cutaneous Melanoma: A Systematic Review and Meta-analysis

Abstract: We performed a systematic review and meta-analysis to examine the relationship between the type of biopsy technique employed in the diagnosis of cutaneous melanoma and 4 clinically important outcomes: melanoma-specific mortality, all-cause mortality, Breslow tumor depth, or melanoma recurrence. Our database was obtained by searching PubMed, Ovid MEDLINE, EMBASE, the Cochrane Database of Systematic Reviews, and the Cochrane Library from inception until December 6, 2019. Studies were identified that compared bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The data presented support the notion that shave biopsy is usually adequate to diagnose at least T1b or thicker lesions, and therefore the overall management of regional lymph node basins and thus melanoma-specific survival is unchanged. In their meta-analysis, Shellenberger et al compared punch biopsy with excision biopsy 35 and found no significant difference in Breslow thickness, melanoma recurrence, or melanoma-specific mortality. They reported a higher rate of all-cause mortality among the punch biopsy group (RR 1.5; p = 0.02); however, the authors noted that two of the three studies included in their meta-analysis were biased towards older patients in the punch biopsy group, which the authors felt may explain this finding.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented support the notion that shave biopsy is usually adequate to diagnose at least T1b or thicker lesions, and therefore the overall management of regional lymph node basins and thus melanoma-specific survival is unchanged. In their meta-analysis, Shellenberger et al compared punch biopsy with excision biopsy 35 and found no significant difference in Breslow thickness, melanoma recurrence, or melanoma-specific mortality. They reported a higher rate of all-cause mortality among the punch biopsy group (RR 1.5; p = 0.02); however, the authors noted that two of the three studies included in their meta-analysis were biased towards older patients in the punch biopsy group, which the authors felt may explain this finding.…”
Section: Discussionmentioning
confidence: 99%
“…However, when lesions are extensive or excisional biopsy is not possible, incisional or punch biopsies or shave biopsies are reasonable alternative for establishing the diagnosis. 41 The diagnosis of scalp melanoma is usually possible on clinical and dermoscopy examination; however, a definitive diagnosis is confirmed on histopathological examination only. Dermoscopy and RCM can be very useful tools in making a clinically accurate diagnosis and eventually guide the selection of the best area to biopsy in case of large and extensive lesions.…”
Section: Managementmentioning
confidence: 99%
“…Dermoscopy is a technique that uses cross-polarized light and a magnifier placed on skin covered with liquid to see structures in the epidermis and superficial dermis that are not visible to the naked eye, thus allowing for better recognition of the signs of melanoma ( Ankad et al, 2020 ). If the lesion requires additional investigation, an incisional (partial) or excisional (complete) biopsy is performed for histology, with excisional biopsy being the standard of care ( Shellenberger et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%